Mathematical knowledge for teaching evidenced in prospective Mathematics teachers’ reflective writing (Research, Society and Development, 2022)
This article presents results of an investigation that aimed to identify Mathematical Knowledge for the Teaching of future Mathematics teachers evidenced in reflective writing. Conducted from a qualitative and interpretive perspective, the referred research took a look at reflective writings of future mathematics teachers. The analyzis were based on considerations about Reflective Writing and its contributions to teacher training, and Mathematical Knowledge for the Teaching of Ball, Thames and Phelps (2008). Through them, it was possible to identify, among others, that the undergraduates have reflected on their future as Mathematics teachers, indicating possible difficulties or opportunities to apply the strategies recognized in classes; presented some difficulty / failure / weakness in relation to its content or teaching, indicating a possible cause and possibility in how they could overcome them; to build an inventory of actions present in the reflective writings of the undergraduate students, which made it possible to identify Mathematical Knowledge for Teaching.